E-Commerce Design with Business Model Canvas and to Increase Sales using Seo at A Food Store - Dhiaulhaq Majeed; Havy Destiana; Indri Handayani; Aditya Ilham Setyobudi; Rizkq Maulansyah Altaufik (International Institute for Advanced Science & Technology (IIAST), 2023)
This research focuses on a food store that faces several problems, as it still uses manual methods such as a slow product ordering process. Currently, the seller has to manually determine the product price, check the stock availability, and confirm it to the customer, which causes the transaction time to be longer. In addition, there are issues with data recording errors and the risk of losing information on paper records that are also used manually. To overcome these problems, this food shop intends to build an e-commerce business through a website. The approach chosen is to utilize a content management system (CMS), specifically using WordPress as the CMS and for the method using the waterfall method. CMS allows the creation, organization, distribution, publication, and maintenance of corporate or institutional information without requiring expertise in HTML coding. WordPress is very easy to use and easy to access. The proposed solution involves analyzing business processes using the Business Model Canvas (BMC) approach and then building an e-commerce business by designing a website based on CMS, specifically WordPress. This e-commerce website will transform the conventional business model into an online business model, facilitate increased product sales, minimize data recording errors, and generate sales reports using a database for information storage. In creating a website using wordpress which is assisted by the waterfall method which hopes to have an interface and tools that can make it easier for users to use. In addition, this system will provide customers with an efficient online ordering experience and easy access to product information, thereby increasing the efficiency of the purchasing process.